Pengaruh Pemberian Posisi Pronasi Terhadap Oksigenisasi pada Bayi BBLR dengan Ventilasi Mekanik di Ruang Nicu Bunda Aliyah - Tiurlina Zai; Risdiana Rani (Universitas Malahayati Lampung, 2023)
ABSTRACT LBW is a baby who at birth weighs less than 2,500 grams. Pronation is the position in which a support is placed between the shoulder and the iliac crest, so that the movement of the abdomen and the expansion of the chest are free, giving the prone position to LBW babies can increase oxygenation, the implementation of the prone position at the BA hospital has not been carried out routinely, only based on the needs of the baby. to determine the effect of pronation position on oxygenation in LBW infants with mechanical ventilation in the Bunda Aliyah NICU. Research Methods: This type of research is Quasi Experiment with the Type one Group Pre-test and post-test design approach. The population of all neonatal patients treated in the NICU with a sample of 25 respondents. Birth weight (mean: 2062.7) was male with VCMV ventilation mode. The results of the Spired T-test showed that there was a significant difference in giving the prone position in premature infants to Oxygenation p=value: 0.000 (Pvalue0.05). There is a difference in pvalue for each intervention 1st, 2nd and 3rd based on BBL (0.167) ± (0.122) ± (0.029); Gender (0.223) ± (0.057) ±(0.067); type of ventilator (0.043) ± (0.239) ± (0.081). That giving the baby a prone position has an effect on oxygenation. Thus giving the prone position is a non-pharmacological strategy that is effective, safe and affordable for all levels of society to increase oxygenation in premature infants. Pronation can be used as a treatment modality to increase oxygenation in the hospital. Keywords: LBW, Pronation, Oxygenation ABSTRAK BBLR merupakan bayi yang saat lahir dengan berat badan kurang dari 2.500 gram. Pronasi merupakan posisi dimana ditempatkannya penyanggah di antara bahu dan pada krista iliaka, supaya pergerakan abdomen dan ekspansi dada bebas, pemberian posisi pronasi pada BBLR dapat meningkatkan oksigenisasi, intervensi pemberian posisi pronasi di rumah sakit Bunda Aliyah belum di lakukan secara rutin hanya berdasarkan kebutuhan bayi saja . Mengetahui pengaruh pemberian posisi pronasi terhadap oksigenisasi pada bayi BBLR dengan ventilasi mekanik di ruang NICU Bunda Aliyah. Jenis penelitian Quasi Eksperimen dengan pendekatan Tipe one Group Pre-test and post-test design. Populasi semua pasien neonatus yang di rawat di NICU yang memenuhi kriteria inklusi penelitian dengan sampel 25 responden. Berat badan lahir (mean: 2062,7) laki-laki (51,6%) dengan mode ventilator VCMV (72,0%). Hasil Hasil uji T-test Spired terdapat perbedaan signifikan pemberian posisi pronasi pada bayi prematur terhadap Oksigenasi p=value: 0,000 (Pvalue0,05). Terdapat perbedaan pvalue setiap intervensi ke 1, 2 dan 3 berdasarkan BBL (0,167) ± (0,122) ± (0,029); Jenis Kelamin (0,223) ± (0,057) ±(0,067); jenis ventilator (0,043) ± (0,239) ± (0,081). Bahwa pemberian pemberian posisi pronasi pada bayi memiliki pegaruh pada oksigenasi. Dengan demikian pemberian posisi pronasi merupakan strategi nonfarmakologis yang efektif, aman dan terjangkau oleh semua lapisan masyarakat untuk peningkatan oksigenasi pada bayi prematur. Pronasi bisa dijadikan sebagai modalitas pengobatan penujang peningakatan oksigenasidi rumah sakit. Kata Kunci: BBLR, Pronasi, Oksigenasi